2015
DOI: 10.1152/japplphysiol.01144.2014
|View full text |Cite
|
Sign up to set email alerts
|

M-wave potentiation after voluntary contractions of different durations and intensities in the tibialis anterior

Abstract: The study was undertaken to provide insight into the mechanisms underlying the potentiation of the muscle compound action potential (M wave) after conditioning contractions. M waves were evoked in the tibialis anterior before and after isometric maximal voluntary contractions (MVC) of 1, 3, 6, 10, 30, and 60 s, and after 3-s contractions at 10, 30, 50, 70, 90, and 100% MVC. The amplitude, duration, and area of the first and second phases of the M wave, together with the median frequency (Fmedian) and muscle fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…The reason for these contrasting effects between M MAX P‐P and Area, and thus also the greater efficacy of M MAX P‐P for normalization purposes may reflect the differences in the nature of these measurements. M MAX P‐P is a measure of amplitude, whereas M MAX Area is dependent on both amplitude and duration, thus our finding might indicate that absolute EMG MVT depends primarily on signal amplitude rather than duration. Previous studies have only examined spatial distribution of M‐wave amplitude, during sub‐maximal stimulation and found the amplitude to be both higher and lower at distal sites in gastrocnemius.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The reason for these contrasting effects between M MAX P‐P and Area, and thus also the greater efficacy of M MAX P‐P for normalization purposes may reflect the differences in the nature of these measurements. M MAX P‐P is a measure of amplitude, whereas M MAX Area is dependent on both amplitude and duration, thus our finding might indicate that absolute EMG MVT depends primarily on signal amplitude rather than duration. Previous studies have only examined spatial distribution of M‐wave amplitude, during sub‐maximal stimulation and found the amplitude to be both higher and lower at distal sites in gastrocnemius.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, M MAX may be particularly useful as an independent reference for normalization of sEMG during maximum voluntary isometric contractions (MVCs); given that the most widely used voluntary reference task (MVCs) are not valid in this case (ie a variable normalized to itself) . Both M MAX amplitude (ie peak‐to‐peak, M MAX P‐P) and area (M MAX Area), which is dependent on both amplitude and duration of the evoked potentials, have been suggested/used as reference normalization measurements for voluntary sEMG . Although M MAX normalization of voluntary sEMG has been demonstrated to reduce between‐participant variability it is currently unknown if M MAX normalization of voluntary EMG recordings: (a) removes the influence of electrode location across the surface of the muscle on voluntary sEMG amplitude, and (b) removes the influence of MED on voluntary sEMG amplitude between‐participants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have recently shown that the M‐wave second phase augmented transitorily during the 15 s period following a 3 s MVC, with the maximum increase being reached 1 s after the contraction (Rodriguez‐Falces et al. ). Therefore, by choosing the post‐contraction M‐waves as control responses, it was ensured that both the control M‐waves and the M‐waves evoked during the fatiguing protocol (see below) were obtained under the same contraction history conditions, namely, 1 s after each MVC.…”
Section: Methodsmentioning
confidence: 93%
“…Peak‐to‐peak duration (Dur PP ) was computed as the time interval between the first and second peaks of the M‐wave. Changes in Ampli FIRST and Area FIRST were expected to reflect alterations in membrane excitability, whereas Ampli SECOND and Area SECOND could be influenced by changes in muscle architectural features as well as in sarcolemmal excitability (Rodriguez‐Falces et al., ). Changes in Dur FIRST , Dur SECOND and Dur PP were assumed to follow alterations in muscle fibre conduction velocity (Bigland‐Ritchie et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of stiffness and muscle architectural changes (Gago et al, 2014a; Rodriguez-Falces et al, 2015), acute enhancements of twitch parameters such as peak torque (PT) and the rate of torque development (RTD) and relaxation (RTR) after an MVIC might be mainly related to enhanced cross-bridge cycle efficiency (Brito et al, 2011; MacIntosh 2010; Stull et al, 2011). PAP can be affected by fiber type composition of the muscle, but the intensity of the conditioning contraction and the muscle length also greatly affect the degree of PAP (Rassier et al, 1997; Tillin and Bishop, 2009).…”
Section: Introductionmentioning
confidence: 99%